Coloclyster of Red Peony Root Granules Alleviates Moderately Severe Acute Pancreatitis: A Double-Blinded, Placebo-Controlled, Randomized Clinical Trial. (23rd July 2020) - Yang, Fangyong; Qi, Xiuzhong; Du, Yiqi; Chen, Yan; Wang, Meitang; Huang, Haitao; Zhu, Dezeng; Yue, Xiaoqiang; Wang, Lina
Abstract : The red peony root derived from Paeonia lactiflora has been applied to treat human inflammatory diseases. To investigate its therapeutic potential in treating moderately severe acute pancreatitis (MSAP), which has been rarely studied, this study was designed as a double-blinded, placebo-controlled, randomized clinical trial. A total of 60 MSAP patients were enrolled and randomly divided into an experimental ( n  = 30) group and a control group ( n  = 30), who received a coloclyster of 15 g of red peony root or placebo granules dissolved in 150 mL of water, respectively. The patients' demographic and clinical characteristics were recorded. The results showed that the experimental group had a shorter remission time of fever (p < 0.05 ) and abdominal pain (p < 0.01 ) and faster resumption of self-defecation (p < 0.01 ) than did the control group. In addition, the coloclyster of red peony root decreased the modified Balthazar CT score as well as the serum interleukin-6 and tumor necrosis factor-alpha levels to a greater extent than did the placebo coloclyster (p < 0.05 ). The remission times for the normalization of white blood cells and percentage of neutrophils and lymphocytes in the experimental group were also significantly shorter than those in the control group (p < 0.05 ). In conclusion, a coloclyster of red peony root could help alleviate the clinical symptoms and shorten the course of MSAP by possibly attenuating systematic inflammation. This trial is registered with 14004664 .